Analysis of Template Variations on RNA Synthesis by Respiratory Syncytial Virus Polymerase - Dongdong Cao; Inesh Gooneratne; Cristopher Mera; Jenny Vy; Maurice Royal; Bozun Huang; Yuri Park; Ambika Manjunath; Bo Liang (Viruses, 2022)
Respiratory syncytial virus (RSV) is a significant threat to infants and elderly individuals globally. Currently, there are no effective therapies or treatments for RSV infection because of an insufficient understanding of the RSV viral machinery. In this study, we investigated the effects of the template variations on RNA synthesis by the RSV polymerase through in vitro RNA synthesis assays. We confirmed the previously reported back-priming activity of the RSV polymerase, which is likely due to the secondary structure of the RNA template. We found that the expansion of the hairpin loop size of the RNA template abolishes the RSV polymerase back-priming activity. At the same time, it seemingly does not affect the de novo RNA synthesis activities of the RSV polymerase. Interestingly, our results show that the RSV polymerase also has a new primer-based terminal extension activity that adds nucleotides to the template and primer in a nonspecific manner. We also mapped the impact of the RNA 5′ chemical group on its mobility in a urea-denaturing RNA gel shift assay. Overall, these results enhance our knowledge about the RNA synthesis processes of the RSV polymerase and may guide future therapeutic efforts to develop effective antiviral drugs for RSV treatment.